2021
DOI: 10.1094/phyto-08-20-0326-r
|View full text |Cite
|
Sign up to set email alerts
|

Role of Penicillin-Binding Proteins in the Viability, Morphology, Stress Tolerance, and Pathogenicity of Clavibacter michiganensis

Abstract: Previous research has shown that penicillin-binding proteins (PBPs), enzymes involved in peptidoglycan (PG) assembly, could play an important role during the induction of viable but non-culturable (VBNC) state, which allows non-spore forming bacteria to survive adverse environmental conditions. The current study found that C. michiganensis has a total of seven PBP proteins. Mutant analysis indicated that deletion of either of the class B PBPs was lethal, and that the class A PBP, PBPC, had an important role in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…S2I and J). These results were consistent with the observation by scanning electron microscopy ( 30 ), and confirmed that the lack of pbpC reduced the bacterial resistance to Cu 2+ in C. michiganensis .…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…S2I and J). These results were consistent with the observation by scanning electron microscopy ( 30 ), and confirmed that the lack of pbpC reduced the bacterial resistance to Cu 2+ in C. michiganensis .…”
Section: Resultssupporting
confidence: 91%
“…It has been proved that loss of pbpC had significantly reduced survivorship of VBNC cells induced by Cu 2+ and also increased the sensitivity to a series of stress treatments in C. michiganensis ( 30 ). To evaluate whether pbpC is required for stress resistance in VBNC state, the mutant ΔpbpC was induced into VBNC state, followed by ultrasonication treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The utility of two-step systems has been demonstrated in other actinobacteria 108 including Rhodococcus and Streptomyces bacteria as well as other Gram-positive 109 bacteria (Dubeau et al 2008;Kostner et al 2017;Chen et al 2020;Savory et al 2020).…”
Section: Pselact-ko System For Markerless Deletions In Clavibactermentioning
confidence: 99%